Functional Outcome of Fractures of the Distal Third Tibia Treated with Minimally Invasive Plate Osteosynthesis - Manandhar, Rajeev Raj; Khanal, KR; Shah, NK; Gautam, S (Nepal Orthopaedic Association Journal, 2021)
Background: The management of distal tibia fractures remains challenging. The precarious soft tissue over the distal part of tibia makes it prone to skin complications and reduces the blood supply. This can lead to delayed or non-union when treated with conventional plating. The wide medullary canal makes it difficult to control and maintain the reduction if treated with intramedullary nails. A relatively new technique of minimally invasive percutaneous plate osteosynthesis is thought to overcome the shortcomings of both of these techniques.Method: A prospective study was designed to evaluate the functional outcome of minimally invasive plate osteosynthesis in 25 patients with metaphyseal and simple articular fractures of distal tibia in a tertiary centre from July 2020 to December 2021. The functional outcome was assessed with American Orthopaedic Foot and Ankle Society score at six months and the radiological union was assessed on radiographs.Result: There were 12 male and 13 females in the study with mean age of 46.4± 11.84. The mean American Orthopedic Foot and Ankle Society score was 93.84 ± 6.15. All fractures united within the study period with mean time to union of 21.04 ± 8.739 weeks.Conclusion: Minimally invasive plate osteosynthesis is a reliable technique for the treatment of distal tibia fractures with good functional outcome.